2023
DOI: 10.1186/s13023-023-02657-x
|View full text |Cite
|
Sign up to set email alerts
|

Parent-reported phenotype data on chromosome 6 aberrations collected via an online questionnaire: data consistency and data availability

Abstract: Background Even with the introduction of new genetic techniques that enable accurate genomic characterization, knowledge about the phenotypic spectrum of rare chromosomal disorders is still limited, both in literature and existing databases. Yet this clinical information is of utmost importance for health professionals and the parents of children with rare diseases. Since existing databases are often hampered by the limited time and willingness of health professionals to input new data, we coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…11 In our cohort, consisting of mainly individuals not previously described, only mildly dilated lateral ventricles were reported in more than one individual. Although these results should be interpreted cautiously since brain abnormalities seem to be under-reported by parents, 13 mildly dilated lateral ventricles were reported before, 4 as were other nonspecific and non-significant abnormalities without implication for management or prognosis. 5 Lozano et al recommend brain imaging in all newly diagnosed individuals with FOXP1 syndrome.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…11 In our cohort, consisting of mainly individuals not previously described, only mildly dilated lateral ventricles were reported in more than one individual. Although these results should be interpreted cautiously since brain abnormalities seem to be under-reported by parents, 13 mildly dilated lateral ventricles were reported before, 4 as were other nonspecific and non-significant abnormalities without implication for management or prognosis. 5 Lozano et al recommend brain imaging in all newly diagnosed individuals with FOXP1 syndrome.…”
Section: Discussionmentioning
confidence: 62%
“…21 Engwerda previously showed that parent-reported data may give new insight into clinically relevant symptoms not previously detected. 13 Although we cannot be sure that the symptoms rated by parents as most burdensome represent the perspective of the patient, they will provide the most representative and useful source of information, as recognised within the field of paediatrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation